How mechanochemistry affects the composition and properties of disordered fluorite BaSnF4? - Mercadier, Briséïs; Legein, Christophe; Duttine, Mathieu; Body, Monique; Gutierrez, Ana Gabriela Porras; Leclerc, Sandrine; Lebedev, Oleg; Masquelier, Christian; Dambournet, Damien (Comptes Rendus. Chimie)
Mechanochemistry has been widely used to enable the formation of homogenous mixed phases, particularly in the field of fluoride ion conductors. In this work, we have investigated the effect of applying long duration time of high energy ball milling on the formation of disordered fluorite BaSnF4. We have systematically compared the properties of two samples, one prepared using a commonly reported protocol and one obtained after a longer duration. Microstructural analysis obtained by X-ray line refinement and Williamson–Hall diagrams showed that increasing the ball milling time resulted in a decrease in particle size from 13 to 6 nm and suppressed the occurrence of microstrains, which were identified as twinned regions by microscopy analysis. Prolongation of the ball milling treatment is also associated with a decrease in ionic conductivity with identical fluoride ion jump activation energy. 119Sn Mössbauer spectroscopy revealed the presence of a new signature assigned to Sn(IV) in an oxide–fluoride environment. We hypothesized that this new environment originates from the formation of an anion-excess fluorite-type phase $BaSn_{1-x}^{(II)}Sn_{x}^{(IV)}F_{4}O_{x}$ induced by prolonged milling. Such a hypothesis is supported by the occurrence of fluoride ions located within octahedral sites, which are likely to be bound to Sn(IV) resulting to their lower mobility as shown by 19F solid-state NMR. Overall, this work demonstrates that the interplay between the microstructure, composition and the transport properties of fluoride ion conductors is indeed complex, with many factors at play, including size, strain, defects or composition.